An empirical analysis of cultural inheritance and ICT role on learning practice in a working environment; A PLS-SEM analysis - Guanghui, Feng; Meng, Zhou; Delin, Huang (Frontiers in Environmental Science, 2022)
A review of the relevant research reveals that the concept of "professional growth" is understood to refer to an all-encompassing developmental process that occurs throughout a person's career as well as their entire life, and it is acknowledged as a phrase that is connected to other ideas. In addition, we can say that human attributes and circumstances are not the only factors that play a role in the process of professional development, but social and institutional experience also play a role in it. After that, this research is shown, which has personal dimensions for beliefs (B), co-workers (CW), culture inheritance (CI), customs (C), information and communications technology (ICT), and learning practice (LP). The research is formed to illustrate that promotion of professional growth in workplaces is connected to the mentioned variables. This study was based on the working experience of different backgrounds people. We tried to check how their attributes could influence their working practices and learning practices. A semi-structured questionnaire was adopted from existing literature and modified as per the study area. B > LP (= 0.022; p 0.010), CI-> LP (= 0.368; p 0.000), C-> LP (= 0.210; p 0.000), and ICT-> LP (= 0.410; p 0.000) were found to be significant using PLS-SEM direct path analysis.These results offer support to hypotheses H1, H3-H6 accepted and H2 rejected. As control variables, we looked at the respondents' age, education, and gender. Gender (= 0.006; p 0.846) showed insignificant relationships with LP, whereas age (= -0.103; p 0.001) and education (= -0.072; p 0.034) showed significant relationships with the dependent variable. gender does not have any relationship with learning practices (LP), but age and education can be favorable control variables, and an aged and experienced person can have more impacts on LP and impacts on independent variables.